Tuning the performances of perovskite solar cells using effective organic molecular hole-transporting materials: a review - Zou, Xiu-Wen; Guo, Piao; Zhou, Ying-Ying; Luo, Yi-Ming; Li, Yuan-Yuan; Yang, Qi-Yuan (Frontiers in Chemistry, 2025)
This review discusses the current designs and synthetic procedures for organic small molecules as hole-transporting materials (HTMs) by focusing on their structure–property correlations, short-circuit current density (Jsc), open-circuit voltage (Voc), fill factor (FF), power conversion efficiency (PCE), and material optimizations. While optimizing non-planar spiro-like compounds, various conjugated aromatic, planar molecules, and even porphyrin metal complexes have been developed and studied for the generation of new HTMs. Heteroatoms like oxygen, sulfur, nitrogen, silicon, and selenium have been proven to be beneficial for the development of more stable and cost-effective HTMs and perovskite solar cells (PSCs). Thus, developing new organic molecules as HTMs or HTM dopants can be considered a viable approach for PSCs. A deeper understanding of the organic small molecular perovskites/HTMs can also provide insights into the design of novel molecular architectures capable of achieving effective and stable PSC systems. Finally, we present the outlook for further developments of conventional PSCs with organic molecular HTMs.